Kultura gospodarcza w gminach. Próba doboru mierników - Polski, Jan ("Economic Culture in Gminas Attempt of Indexes Selection", 2007)
The article emphasizes the fact that the essence of economic culture is the level of knowledge and abilities, material standards of economy and also the ability to implement innovations favourable for the development of defined area (in gamins). The author attempts to identify the economic-•cultural indexes of application in local policy. He distinguishes three groups: 1) objective, in the following spheres: knowledge and abilities, achieved material standards and accustoming of innovations; 2) subjective, separating the economic subjects, households and public economy; 3) investments and exploitation (use). The attempt the constructing economic-cultural indexes was undertaken in favour of local development policy.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 272-281